Estimativa dos fluxos de calor sensível e latente através do método de covariância de vórtices turbulentos em área de campo sujo na baixada cuiabana - Santanna, Franciele Bomfiglio (2013)
The main goal of this thesis was to estimate the sensible (H) and latent (LE) heat flux using the eddy covariance method in a Cerrado "Campo Sujo" area, basically with herb-shrub physiognomy, sparse woody vegetation and approximately 2m height. The geographical position of the Cerrado, altitude, latitude, longitude, climate and weather conditions are determined by the dynamics of the atmosphere that affects the whole South America and consequently influence the ecological framework of ecosystems. The results shown by the components considered in the energy balance were more significant during the day, which the atmospheric boundary layer extends from the ground to about 50 or 100 meters height, showing greater instability and turbulence (u* ˃ 0.2 m / s), and this turbulence is what justifies the use of the eddy covariance method to estimate the sensible and latent heat flux. The Cerrado presents seasonal difference between the densities estimates of sensible (H) and latent (LE) heat flux. During the rainy season the sensible heat flux (H) was 25% and the latent heat flux (LE) 54%. During the dry season the sensible heat flux (H) was 42% and the latent heat flux (LE) 30% of the energy budget.